The pianist - Polanski, Roman; Benmussa, Robert; Sarde, Alain, 1952-; Harwood, Ronald, 1934-; Brody, Adrien; Kretschmann, Thomas, 1962-; Finlay, Frank, 1926-2016.; Lipman, Maureen; Fox, Emilia, 1974-; Stoppard, Ed.; Rayner, Julia; Meyer, Jessica Kate.; et al. (Universal City, Califonia : Universal, 2003)
Based on the memoirs of Wladyslaw Szpilman, a Polish Jew, who was a brilliant pianist. He watched as his family was shipped off to Nazi labor camps. He managed to escape and lived for years in the ruins of Warsaw, hiding from the Nazis.
Based on the memoirs of Wladyslaw Szpilman, a Polish Jew, who was a brilliant pianist. He watched as his family was shipped off to Nazi labor camps. He managed to escape and lived for years in the ruins of Warsaw, hiding from the Nazis.
Based on the book Smierc miasta by Wladyslaw Szpilman.
Videodisc release of a 2002 motion picture.
Special features: "A story of survival" featurette which includes insight into the making of the film, Roman Polanski's own story of survival during WWII, behind-the-scenes interviews with Oscar winners Roman Polanski, Adrien Brody and Ronald Harwood, clips of Wladyslaw Szpilman playing the piano.
Director, Roman Polanski ; director of photography, Pawel Edelman ; editor, Herve de Luze ; music, Wojciech Kilar.
Adrien Brody, Thomas Kretschmann, Frank Finlay, Maureen Lipman, Emilia Fox, Ed Stoppard, Julia Rayner, Jessica Kate Meyer.
MPAA rating: R, for violence and brief strong language.
Keywords: Szpilman, Wladyslaw -- Drama; Jews -- Poland -- Warsaw -- Biography; Holocaust, Jewish (1939-1945) -- Poland -- Warsaw -- Personal narratives; Jewish musicians -- Poland -- Warsaw -- Biography; Feature films; Films for the hearing impaired